Actividades desconectadas para apoyar al pensamiento computacional en la asignatura de Lengua y Literatura, para el quinto grado de educación general básica de la Unidad Educativa Emiliano Ortega Espinoza de la ciudad de Catamayo, provincia de Loja, año lectivo 2021-2022. - Medina Vaca, Jhonny Alexander (2023)
Recent years have seen Computational thinking as an alternative approach to improving educational quality by teaching students computer skills, either in a connected or disconnected way using daily school materials. This project aims to describe disconnected activities to support computational thinking in the subject of Language and Literature during the third semester of the subject, of the fifth-grade students from classroom A, of the "Emiliano Ortega Espinoza" primary school in the city of Catamayo, province of Loja, across the school year 2021- 2022. This study is quantitative with a descriptive/exploratory scope, and the specific population consists of 30 types of activities. For data collection, an ad hoc characterization matrix was prepared, based on the Iglesias and Bordignon's taxonomy of disconnected activities. These activities were selected using the Checklist technique, considering the following parameters: disconnected activities and computational thinking, playful, transversal skills and algorithmic thinking, with a YES or NO evaluation. The results obtained show that, out of the 30 activities, all of them are disconnected, of which 17 activities are directly applicable and 13 allow to be adaptable within the classroom and support computational thinking in the subject of Language and Literature. It is concluded that the process of classification of activities carried out in the research can be applied to other subjects of the national curriculum of education; also, according to the characteristics of the disconnected activities different authors agree on the following: not requiring the use of a computer for their development and execution, and not being linked to technology. Keywords: Computational thinking, disconnected activities, language and literature, middle school.